2020
DOI: 10.1177/1467358420966035
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating collaboration and community participation in tourism development: The case of South-Eastern Nigeria

Abstract: Collaboration and community participation are crucial for securing sustainable tourism and highlight the need to listen and respond to the broad range of stakeholders’ voices, opinions, and concerns. These concepts dominated the discourse of sustainable-responsible tourism and gave rise to collaboration theory as well as various types of community participation. Many scholars in both Western and emerging economies have employed these concepts; however, there is limited research on how they apply in the Nigeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Our assertion is consistent with the views of Brida et al (2014) about tourism having positive socio-cultural impacts on local culture. Similarly, Eyisi et al (2021a) found that the Igbo people identified respect for their culture as one of the strategies for gaining their support and participation in tourism. To glocalize tourism in the region, developers and planners need to understand that the world operates in a two-way exchange of ideas between global and local forces (Soulard and McGehee, 2017).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our assertion is consistent with the views of Brida et al (2014) about tourism having positive socio-cultural impacts on local culture. Similarly, Eyisi et al (2021a) found that the Igbo people identified respect for their culture as one of the strategies for gaining their support and participation in tourism. To glocalize tourism in the region, developers and planners need to understand that the world operates in a two-way exchange of ideas between global and local forces (Soulard and McGehee, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Such empowerment is a way of glocalizing tourism. Elsewhere, Eyisi et al (2021a) found that among other benefits expected by residents in Southeastern Nigeria from tourism, they demanded to boost security and revive their culture because of the insecurity and religious challenges in the region. The implication is that these residents would likely support the type of tourism that addresses these issues and antagonize tourism if it worsens the situation.…”
Section: Literature Review On Glocalization and Tourism Developmentmentioning
confidence: 99%
“…They are also critical in successful tourism development, such that destination managers and other authorities in the tourism industry must consider youths' voice in tourism planning. The involvement of youths is indeed crucial to implementing responsible tourism, as their attitude may directly affect the development of the tourism sector (Eyisi et al, 2020). However, they are often excluded from the decision-making process (Seraphin et al, 2020) and lack the support to fully utilise their potential.…”
Section: Innovationmentioning
confidence: 99%
“…Some literature reviews (Calero and Turner, 2020) have discovered that research in the field of regional economy and tourism as a factor of regional economic development is insufficient, which mostly deals with regional economic development and tourism, using descriptive analysis. According to Rahman and Salahudin (2021), the main topics examined in relation to tourism and regional development nowadays are sustainable development (Candia et al, 2020;Eyisi et al, 2020;Hengky and Kikvidze, 2020;Saneinia et al, 2020;Ivars-Baidal et al, 2021;Tanaka et al, 2021), innovation (Kalvet et al, 2020;Ratnasari et al, 2020;Syapsan and Diartho, 2020;Casanova Enault et al, 2021) local governments (Brillo, 2020;Caaman ó-Francó and Sua rez, 2020;Nel and Connelly, 2020;Prathama et al, 2020;Almeida and Silveira, 2021) and the local communities, residents (Anandhyta and Kinseng, 2020;Hui et al, 2020;Nguyen et al, 2020). Although there are numerous empirical research papers that have attempted to measure the effects of various factors influencing tourism development and regional development in general, very few of them have followed a formal theoretical framework.…”
Section: Tourism and Regional Developmentmentioning
confidence: 99%